Feasibility of Risalad Fruit Salad in West Cikarang: Marketing and Operational Perspectives - Halim, M. Irsyad; Soraya, Nabila; Fazri, Naufal; Silvia, Nita; Amelia S, Putri (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study reflects the importance of a thorough analysis of marketing, operational, and legal aspects in determining the feasibility of the Risalad fruit salad business in West Cikarang. This study aims to include a comprehensive analysis of the marketing, operational, legal, pricing, and promotional aspects of the Risalad business, with the aim of providing insight into its feasibility and potential success in the market. This study applies a qualitative approach, which means focusing on verbal and descriptive data collection. This approach allows researchers to explore information in depth and gain a better understanding of the phenomenon under study. The results of this study provide in-depth insights into the marketing, operational, and legal aspects that influence the feasibility of the Risalad fruit salad business in West Cikarang.